Evaluation of strengthening techniques of traditional masonry buildings: case study of a four-building aggregate - Vicente, Romeu
Increasing appraisal of the durability, conservation state, and changeable use and function of old buildings in urban centers relies a great deal on the structural safety evaluation of vertical load capacity and the ability to resist horizontal forces. The need to assess seismic vulnerability, particularly of traditional masonry buildings, is a key issue. Evaluation of the seismic vulnerability of old buildings is essential in the definition of strengthening needs and minimization of damage from seismic actions in the safeguarding of built heritage. A three-dimensional model was developed for an aggregate of four traditional masonry buildings located in the old city center of Coimbra, in Portugal. The finite element modeling of these buildings has aimed to identify structural fragility, understand the damages detected, and evaluate the global structural safety of these types of buildings. The primary results obtained in this case study helped to interpret the structural damage and stress distribution, and verified global stability and its consequences. Different strengthening techniques to improve the global behavior of these buildings were modeled and analyzed. A comparison of the efficiencies of strengthening strategies is also discussed. DOI: 10.1061/(ASCE)CF.1943-5509.0000164. (C) 2011 American Society of Civil Engineers.